Perancangan Video Feature Jejak Sejarah Peninggalan Perang Dunia II di Biak, Papua - anthony yudhie tumimomor (Jurnal Desain Komunikasi Visual Asia, 2019)
Abstract: World War II events that occurred on the island of Biak Papua, leaves many historical traces that are able to visit and access by people, one of them is the historical site of Binsari Cave, Binsari Cave is a silent witness of terribleness and war’s ferocity, where thousands of Japanese soldiers died killed, because of bombarded by the Allies. Based on observations done, the information related of the history of World War II that occurred in Biak is still very minimal, therefore information medium in the form of audio-visual video such as documentaries with feature genres, is needed ini order to narrate the actual fact of World War II happened. The design of the feature video uses qualitative method and Linear strategy so that it is expected to produce a more detailed information media, clear content and be able to attract people who are eager to know more about this historical event of World War II happened in Biak Island, as well as providing message to the public or tourists who visit the site to participate in maintaining and preserving historical sites in Biak Papua. Key Word : feature video, Binsari Cave, qualitative, Linear strategy